Evaluación del desempeño docente durante la pandemia COVID 19 de la Institución Educativa de Nivel Inicial N° 157 Victoria Barcia Boniffatti, Iquitos 2021 - Lopez Andrade, Doris del Carmen (2022)
It was the general objective of the investigation to describe the evaluation of teaching performance during the pandemia Covid 19 at the Initial Level Public Education Institution No. 157 Victoria Barcia Boniffatti, in Iquitos during 2021. The methodology considered for this purpose was the type of Descriptive research, adopting a univariate, transversal, and field design. The population considered for the study has been the managers and teachers of the educational institution, who was also considered as a sample, being 43 participants. The questionnaire was validated through expert judgment and the survey technique was adopted to collect the data required by the investigation. It is concluded that teachers from the initial institution No. 157 Victoria Barcia Boniffatti, with respect to his teaching performance during the Covid 19 pandemic, 37.2% is located at the high level, while 53.5% is located at the level Average and only 9.3% at low level. What allows to affirm that most teachers had an acceptable performance in the state of emergency.